2015
DOI: 10.1111/tmi.12479
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to delivery of isoniazid preventive therapy in a cohort of children exposed to tuberculosis in Timor‐Leste

Abstract: Abstractobjectives To evaluate the number and geographic location of children aged <5 years exposed to sputum smear-positive tuberculosis (TB) in Timor-Leste, to determine the proportion evaluated for isoniazid preventive therapy (IPT) and to review the programmatic challenges present in delivering IPT to this cohort.methods A total of 256 consecutive sputum smear-positive TB index cases diagnosed at Bairo Pite Clinic between August 2013 and July 2014 were interviewed about places of residence and household co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
22
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 14 publications
6
22
4
Order By: Relevance
“…Additionally, as compared to our study, a slightly higher IPT initiation rate was reported in South Africa and Ethiopia where initiation of IPT was done in 68% 25 and 64% 26 of the children who were eligible for IPT, respectively. On the other hand, the uptake of IPT in our study was higher than the 37% reported in Ethiopia, 27 33% rate in southern India, 28 the 18% demonstrated in Timor-Leste, 29 the 6% reported in a Malawian study 30 and 22% in Bhopal, India. 31 The high variations in the findings most probably is a reflection of the contextual differences in the settings where the studies were carried out.…”
Section: Discussioncontrasting
confidence: 71%
“…Additionally, as compared to our study, a slightly higher IPT initiation rate was reported in South Africa and Ethiopia where initiation of IPT was done in 68% 25 and 64% 26 of the children who were eligible for IPT, respectively. On the other hand, the uptake of IPT in our study was higher than the 37% reported in Ethiopia, 27 33% rate in southern India, 28 the 18% demonstrated in Timor-Leste, 29 the 6% reported in a Malawian study 30 and 22% in Bhopal, India. 31 The high variations in the findings most probably is a reflection of the contextual differences in the settings where the studies were carried out.…”
Section: Discussioncontrasting
confidence: 71%
“…Although previous studies have demonstrated this potential [22], studies have also demonstrated significant challenges linking new cases to prompt treatment [29] and consistently low uptake of preventive TB treatment [3035]. Similarly, only 25% of eligible contacts evaluated by our program initiated IPT.…”
Section: Discussionmentioning
confidence: 91%
“…A recurring theme throughout the different studies was the burden of travel for caregivers of children that had been advised to complete IPT. While financial cost was an issue for some, the duration of travel from people's homes to the nearest clinic appeared to be the principal issue for many . Seasonal farming demands and other family priorities, particularly for mothers, were often recognised as more important than taking children to the clinic .…”
Section: Discussionmentioning
confidence: 99%
“…In many cultures, preventive treatments are not endorsed and the misconception exists that you do not need medicines if you do not feel sick . Even after receiving health education, many caregivers in the studies reviewed were reluctant to take their children in for screening or IPT initiation because they felt they were healthy and asymptomatic . This is a difficult point of understanding to alter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation